Risk of disability pension in patients following rectal cancer treatment and surgery. Issue 11 (27th July 2015) - Chen, L; Glimelius, I; Neovius, M; Eloranta, S; Ekberg, S; Martling, A; Smedby, K E
Abstract: Background: Aspects of survivorship, such as long-term ability to work, are increasingly relevant owing to the improved survival of patients with rectal cancer. The aim of this study was to assess risk and determinants of disability pension (DP) in this patient group. Methods: Using Swedish national clinical and population-based registers, patients with stage I–III rectal cancer aged 18–61 years in 1995–2009 were identified at diagnosis and matched with population comparators. Prospectively registered records of DP during follow-up were retrieved up to 2013. Non-proportional and proportional hazards models were used to estimate the incidence rate ratio (IRR) for DP annually and overall. Potential variations in risk by demographic and clinical factors were calculated, with relapse as a time-varying exposure. Results: A total of 2815 patients were identified and compared with 13 465 population comparators. During a median follow-up of 6·0 (range 0–10) years, 23·3 per cent of the relapse-free patients and 10·3 per cent of the population comparators received DP (IRR 2·40, 95 per cent c.i. 2·17 to 2·65). An increased annual risk of DP was evident almost every year until the tenth year of follow-up. Abdominoperineal resection was associated with an increased DP risk compared with anterior resection (IRR 1·44, 1·19 to 1·75). Surgical complications (IRR 1·33, 1·10 to 1·62) and reoperation (IRR 1·42, 1·09 to 1·84), but not radiotherapy or chemotherapy, were associated with risk of DP. Conclusion: Relapse-free patients with rectal cancer of working age are at risk of disability pension. Abstract : Higher than expected